Three-dimensional (3D) reconstruction of computed tomography (CT) abdominal images using visualization toolkit (VTK) / Afifah Husna Mat Saad - Afifah Husna, Mat Saad (2020)
A computerized tomography (CT) or computerized axial tomography (CAT) scan combines data from several X-raysito produce a detailed image of structures inside the body. CT scans produce 2D of a “slice” or section of the abdomen but the data can also be used to construct 3-dimensional images. However, CT scan unable to accurately represent the internal structure of soft tissues and soft-tissue lesions. Therefore, using the program in Visualization Tool Kit (VTK) is needed to construct a much more clearer 3D image. To reconstruct 3D images from 2D images of a “slice” or section of abdomen which will be resulting in more accurate CT scanned images that will help medical officer diagnose and plan their treatment more effectively and accurately. A 3D image will be less dependent on human cognitive ability as well as lesser time required for human interpretation, resulting in much easier and more accurate clinical works. Therefore, in this research, 4 different methods of rendering are employed and compared to determine which method shows the clearest 3D reconstruction images. The rendering methods that are utilized in this research are surface rendering, surface rending with multiplanar rendering, volume rendering and volume rendering with additional features. from the analysis, it shows that volume rendering with additional features has advantage in reconstructing the meticulous tissues and bones of abdomen and helps in providing a detailed data by coordinate, measurement and crop feature in order to determine the exact coordinate for lesions located in abdomen, length measurement of the v lesions and crop the outer surface of abdomen to see the inner surface of abdomen, respectively.